UI UX Design of Waste Sorting Website-Based Application Applying the Design Sprint Method Case Study Palmerah West Jakarta - Abiansyah, Adillah Halim; Hanif, Isa Faqihuddin; Fauzan, Muhammad Fathan (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
Public awareness that is increasingly paying attention to environmental problems requires public awareness to manage waste in a more efficient way. Due to the lack of understanding and appropriate methods for sorting waste, solutions different from conventional methods must be sought. Technology has become an important part of innovation in management. User Interface (UI) and User Experience (UX) are increasingly considered important in meeting user needs due to new interaction patterns with technology. The aim of this research is to understand and meet user needs in waste sorting. Therefore, the author has found a solution by creating a UI/UX design for an interactive waste sorting application. This study was conducted using the design sprint method which consists of five steps: understand, differentiate, decide, create a prototype, and verify. The results of tests carried out using the system usability scale method produced a score of 75, which shows that this application makes it easier for users to sort waste more efficiently and environmentally friendly.